Evaluation of Microbial Quality of Fresh Goat Meat Sold in Umuahia Market, Abia State, Nigeria - Eze, V.C.; Ivuoma, Nwosu (Pakistan Journal of Nutrition, 2012)
The evaluation of microbial quality of fresh goat meat sold in Umuahia market Abia State was carried out. A total of 40 samples of fresh goat meat were collected and analyzed for total aerobic plate count, coliform count, Salmonella-Shigella count and fungal count using nutrient agar, MacConkey agar, Salmonella-Shigella agar and potato dextrose agar respectively. The pour plate technique was employed. The total aerobic plate count ranged from 5.39±0.04 Log10cfu/g to 5.48±0.05 Log10cfu/g while the coliform count ranged 4.09±0.01 Log10cfu/g to 4.47±0.05 Log10cfu/g. The Salmonella-Shigella count ranged from 0±0.00 Log10cfu/g to 2.43±0.02 Log10cfu/g while the fungal count ranged from 3.18±0.02 Log10cfu/g to 3.56±0.05 Log10cfu/g. The microorganisms isolated from the fresh goat meat samples were Bacillus species, Escherichia coli, Proteus species, Pseudomonas species, Salmonella species, Staphylococcus aureus, Streptococcus species, Aspergillus species, Penicillium species and yeast. The result showed that goat meats were often contaminated with microorganisms due to unhygienic and poor sanitary conditions.